‘You’re not serving time, you’re serving christ’: protestant religion and discourses of responsibilization in a women’s prison - Ellis, Rachel (The British journal of criminology, 2021)
Criminologists are increasingly concerned with how incarcerated persons navigate dominant carceral discourses. Insights from narrative criminology reveal that individuals draw on a variety of available discursive resources to adopt, subvert or negotiate dominant messages around what it means to be punished. This article draws on yearlong ethnographic observations inside one US state women’s prison to examine whether and how religion matters for responsibilization discourses promoted by state actors. Examining a case study of Protestant prison activities, I find that religious discourses served dual purposes in light of responsibilization. Interpretively, by describing prison as part of God’s plan, they offered a meaningful counterpoint that mitigated punitive discourses from prison officials. In practice, responsibilization discourses, filtered through the coercive carceral context, re-emerged through a normative religious lens with regard to prison rules and state authority. Considered at the intersection of race, class and gender, this article interrogates how women may draw on discourses from competing institutions such as religion in constructing self-narratives and enacting responsibilization, and how this matters for state control.